Implementation of the Principle of Recognizing Service Users for Notary (Study of Application of Article 2, Paragraph (2) Permenkumham No. 9 of 2017 in Malang City - Dian Dombat Pejoreza; Moh Fadli; Rachmi Sulistyarini (PT FORMOSA CENDEKIA GLOBAL, 2023)
The presence of a notary in the midst of society is very important, because a notary can provide guarantees of legal certainty related to making authentic deeds. According to Permenkumham No. 9 of 2017, notaries are required to follow the principle of recognizing service users. This obligation is borne by Reporting Notaries Parties in reporting questionable service users' financial activity as well as a form of protection for Protecting notaries from the risks of money laundering and steps to bolster government initiatives to combat money laundering. However, in implementing this principle there are still several notaries who have not implemented it. The problems studied in this study are related to the effectiveness of implementing the idea of recognizing service consumers in accordance with Permenkumham No. 9 of 2017 as the legal basis of Notaries in Malang City. The research method used is socio-legal with a sociological approach or looking at the implementation of norms in the field. The results of the study show that notaries in Malang are still found not to have implemented PMPJ based on Permenkumham No. 9 of 2017, PMPJ is considered a Notary. then the implementation is not effective, even though the legal substance has provided rules, the implementation of this article is hampered by several factors, namely the Notary Factor itself originating from an internal Notary who does not apply it, does not understand the obligation to apply the Principle of Recognizing a Service User (PMPJ) based on Permenkumham No. 9 of 2017, Inadequate facilities, notary's lack of understanding regarding how to control/use the IT system, and there are no strict sanctions from the Ministry of Law and Human Rights against notaries who do not implement PMPJ